Richard Fox of St Albans - Anna Probert (Medievalista)
In 1448, Richard Fox, a lay man employed by St Albans Abbey, completed a substantial prose chronicle of British and Continental affairs. This article examines what is known about Fox, first by giving an overview of the Chronicle and the manuscript in which it appears and also by appraising three key sources: his will of 1454, his literary miscellany and his appearance in the annals of Saint Albans. In doing so it shows the important connections that Fox had, both to medieval book culture and to influential people including Abbot John Whethamstede and translator Eleanor Hull, which may have contributed to his Chronicle.